Utilization of Asset Management in Infrastructure Development in Denpasar City - Bagus Kanaka Kusuma, Ida; Ketut Agusintadewi, Ni (Universitas Ibn Khaldun Bogor, 2024)
Important infrastructure development is carried out to improve the welfare of the people in Denpasar City in various factors. It is necessary to carry out strategic asset planning in infrastructure development so that utilization is appropriate, directed and efficient. The presentation of the results of the analysis of this research data was carried out qualitatively due to research on objects with adjustments to the conditions of events in the present. The results of this study describe that strategic planning of assets in Denpasar City is carried out starting from the stages of identifying assets, evaluating asset conditions, determining needs, strategic planning, setting policy standards, and preparing budgets. These stages are carried out so that infrastructure is built in accordance with the feasibility and needs required for certain communities and organizations.